THE CLINICAL EPIDEMIOLOGY OF NOROVIRUS INFECTION IN CHILDREN WITH DIARRHEA AT REGIONAL PUBLIC HOSPITAL DR.SOETOMO - Alpha Fardah Athiyyah; Sofia Wardhani; Andy Darma; Reza Gunadi Ranuh; Dadik Raharjo; Toshiro Shirakawa; Subijanto Marto Sudarmo (Universitas Airlangga, 2020)
Background: Norovirus has become a major cause of severe outbreaks of gastroenteritis since the discovery of the rotavirus vaccine, with the main symptom being diarrhea. Until now, research on the epidemiological analysis of norovirus has not been carried out at Regional Public Hospital (RSUD) Dr. Soetomo, Surabaya. Purpose: This study aims to provide clinical epidemiology data and an analysis of norovirus infections in children with diarrhea at Regional Public Hospital (RSUD) Dr. Soetomo, Surabaya, Indonesia, including the prevalence of norovirus infection in each age group and sex, its clinical appearance, and its seasonal variation. Methods: A cross-sectional study was conducted in children aged 1–60 months hospitalized for diarrhea in RSUD Dr. Soetomo between April 2013 and March 2014. Identification of the virus in the stool was done by norovirus enzyme immunoassay Quick NaviTM Noro2. The proportion, age, sex, clinical symptoms, and patterns of the norovirus seasonal data were calculated. Results: Norovirus was detected in 64 samples (19%) of the 340 stool samples, with a mean patient age of 11.75 months; it was mostly found in patients less than 24 months of age (95%), and 64% were male. The monthly pattern of norovirus infection was mostly found in November, followed by May and April. The clinical symptoms were fever (72%), vomiting (66%), bloating (59%), abdominal cramps (34%), perianal inflammation (27%), abdominal distension (16%), and seizures (8%). Conclusion: The prevalence of norovirus was found to be high in patients with diarrhea aged 1–60 months hospitalized in RSUD Dr. Soetomo, with a proportion of 19%. Further research is needed to determine the severity of norovirus infection.